CCARDESA Agribusiness and Gender and Youth Responsive Food Systems - Mwale, Nawa S; Recha, John W.M.; Kakuwa, Bridget; Magagula, Futhi; Maapatsane, Botho (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Centre for Coordination of Agricultural Research and Development for Southern Africa (CCARDESA) is a SADC subsidiary mandated by Members States to coordinate regional cooperation in agricultural research and development. It is implementing the Comprehensive Africa Agriculture Development Programme EX Pillar 4 (CAADP-XP4) Programme on Gender. The CAADP-XP4 Programme is financed through the International Fund for Agricultural Development (IFAD) for four years, between 2019-2023. The CAADP-XP4 programme supports a science-led and climate-relevant agricultural transformation in Africa. It aims at strengthening the capacities of CCARDESA to deliver on their Agricultural Research for Development (AR4D) mandate and to support African countries collectively implementing relevant programmes of the Comprehensive Africa Agriculture Development Programme (CAADP) through inclusive regional and international partnerships; production and exchange of climate-relevant agricultural knowledge; effective communication, monitoring and evaluation; promotion of systemic and effective use of science, knowledge and innovation; and representation of the Sub Regional and National Organizations at Continental level. The programme seeks to achieve outputs, and one of them is to build the capacity of women-led and youth-led organizations to participate in strategic events and global climate issues. This entails enhancing partnerships among the multi-stakeholders across sectors and strengthening capacities of the implementing countries on gender strengthening/capacity to realize the outputs of the programme. One of the roles of the CAADP-XP4 programme is to strengthen and support women and youth in agribusiness for improved livelihood and increased income. As part of accomplishing this key activity, CCARDESA, in collaboration with AFAAS, ASARECA, CORAF and FARA, facilitated a gender-focused side event titled ‘The CCARDESA Fostering Agribusiness and Gender/YouthResponsive Food Systems’ side event at the Science Week in Durban